2021
DOI: 10.3390/ijerph18189784
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution during Pregnancy and Childhood Autism Spectrum Disorder in Taiwan

Abstract: Air pollutants have been linked to some diseases in humans, but their effects on the nervous system were less frequently evaluated. Autism spectrum disorder (ASD) is a group of neurondevelopmental disorders of which the etiology is still unknown. We conducted a study in Taiwan to evaluate the possible associations between prenatal exposure to air pollutants and ASD. From a random sample of one million people in the National Insurance Research Database, we identified all the infants born between 1996 and 2000. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 106 publications
(143 reference statements)
1
7
1
Order By: Relevance
“…Wang et al found that gas pollutants such as nitrogen dioxide (NO 2 ) and carbon monoxide (CO) could influence the whole pregnancy and markedly add to the danger of neonatal DDs through a random-sample survey of 1 million people, hazard ratios (95% CI) of 1.39 (1.22-1.58) and 1.93 (1.55-2.39), respectively. But no relevancy between sulfur dioxide (SO 2 ) and DDs was detected in this study [72] .…”
Section: Congenital Hydrocephaluscontrasting
confidence: 60%
“…Wang et al found that gas pollutants such as nitrogen dioxide (NO 2 ) and carbon monoxide (CO) could influence the whole pregnancy and markedly add to the danger of neonatal DDs through a random-sample survey of 1 million people, hazard ratios (95% CI) of 1.39 (1.22-1.58) and 1.93 (1.55-2.39), respectively. But no relevancy between sulfur dioxide (SO 2 ) and DDs was detected in this study [72] .…”
Section: Congenital Hydrocephaluscontrasting
confidence: 60%
“…Some studies found exposure to CO and NO 2 may associate with immune dysregulation and neuroinflammation (Kalkbrenner et al, 2014;Kelly, 2003). However, others believe that these air pollutants are more likely to be surrogates of traffic-related air pollution rather than a direct cause of neuroinflammation and early neuroimmune system activation (Kim et al, 2014;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found exposure to CO and NO 2 may associate with immune dysregulation and neuroinflammation (Kalkbrenner et al., 2014 ; Kelly, 2003 ). However, others believe that these air pollutants are more likely to be surrogates of traffic‐related air pollution rather than a direct cause of neuroinflammation and early neuroimmune system activation (Kim et al., 2014 ; Wang et al., 2021 ). More clinical studies on examining the impact of more complex traffic‐related pollutants like secondary pollutants formed in the atmosphere and non‐combustion emissions on early activation of the immune system and neuroinflammation are strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that children are particularly vulnerable to air pollution, primarily due to their smaller airways, immature respiratory and immune systems, higher respiratory rate, and relatively high absorption of pollutants [ 7 , 8 ]. Previous epidemiological studies reported an association between exposure to PM2.5 and various health outcomes for children, such as respiratory infections [ 9 , 10 ], asthma [ 11 , 12 ], preterm birth [ 13 , 14 ], low birth weight [ 15 ], growth impairment [ 16 ], and neurodevelopmental [ 17 , 18 ] and metabolic [ 19 ] diseases, all of which can increase mortality risk.…”
Section: Introductionmentioning
confidence: 99%